Complex Interplay: Irritable Bowel Syndrome and the Incidental Discovery of Malrotated Kidney (Bangladesh Journal of Medical Science, 2025)
Background Irritable Bowel Syndrome (IBS) a functional gastrointestinal disorder that, when combined with Iron Deficiency Anaemia (IDA), greatly impacts one’s quality of life. This case study explores the challenges involved in diagnosing and treating a patient with IBS, IDA, and a renal anatomical anomaly. Case Presentation A 29-year-old Saudi woman came in with symptoms suggesting IBS and ongoing IDA despite taking iron supplements. Her medical history revealed a disc prolapse, but there were no signs of gastrointestinal bleedings or dietary deficiencies that could account for the anaemia. During a diagnostic imaging procedure, a malrotated kidney was unexpectedly discovered. Investigations Diagnostic criteria from Rome IV were utilised for diagnosing IBS. The laboratory results indicated IDA, and a CT scan verified the renal abnormality. The management plan involved making dietary adjustments to address IBS and improve iron absorption. Medications were used to alleviate abdominal pain, and both oral and intravenous iron treatments were administered for IDA. The potential impact of the rotated kidney on the patient’s symptoms and anaemia was taken into account, necessitating continuous assessment. Conclusion The case emphasises the significance of taking a comprehensive, interdisciplinary approach when dealing with patients who have intricate gastroenterological symptoms, especially when there are accompanying anatomical irregularities. Furthermore, it highlights the importance of accurate diagnostic methods to identify root causes that may impact the management and outlook of IBS and IDA.BJMS, Volume: 24. Supplementary Issue 2025, Page : 178-182